PERUBAHAN ANTROPOMETRI ANAK USIA SEKOLAH YANG MENGALAMI OBESITAS PASKA PEMBERIAN TERAPI BERMAIN: GOBAK SODOR - Intan Widiastuti; Ika Yuni Widyawati; Erna Dwi Wahyuni (Universitas Airlangga, 2019)
Introduction: Obesity is a metabolic disease in children and adults.gobak sodor play is one of those games that can be given to school-age children to increase physical activity. The purpose of this study was to determine the effect of playing therapy gobak sodor changes in anthropometry school-age children who are obese at SDN Kedungdoro V No.310 Surabaya.Methods: A Quasy Experimental method was used in this study. Population was obese children at SDN Keungdoro V No.310 since May–June 2013. Respondents were 20 children who were taken by purposive sampling. Independent variable was playing therapy:go back through the door. Dependent variable was antropometry. Data were collected by using observation sheet and was analyzed by Paired T-Test and Independent TTestwith significance level of p≤0.05.Result: The result of this study showed that playing therapy: go back through the door had changed BMI and abdominal circumferenceon anthropometric but had no effect on upper arm circumference in school-age children whith obese in SDN Kedungdoro V No.310 Surabaya with t-test. In the treatment group BMI paired t-test p=0.000, abdominal circumference p=0.002 and upper arm circumference p=0.002, while in the control group BMI paired t-testp=0.228, abdominal circumference p=0.168 and upper arm circumference p=0.168, independent ttest BMI p=0.002, abdominal circumference p=0.000 and upper arm circumference p=0.771.Discussion: This concluded that go back through the doorplaying therapy could affect only on BMI and abdominal circumference among obese children. Further research, focus to analyze on confounding factors such dietary and activities on obese children is needed.